PERBANDINGAN KRITERIA MISBRUIK VAN OMSTANDIGHEIDEN / UNDUE INFLUENCE DALAM KONTRAK KONVENSIONAL DAN AKAD BISNIS SYARIAH - Hasanah, Oceania; Wirdyaningsih, Wirdyaningsih (UNES Law Review, 2023)
Abuse of circumstances (Misbruik van Omstandigheiden or undue influence) is an interesting and frequent phenomenon in agreements. Abuse of circumstances can be in the form of a contract in an agreement or a contract used in doing business. Misbruik van Omstandigheiden or undue influence . The agreement of unequal cooperation can occur because there are parties who have a stronger position and are at the top to suppress or threaten the weaker parties. The existence of a bargaining position is the reason why a party in a weak position cannot get freedom of opinion and decide something related to their own interests or common interests. The writing of this article uses qualitative research methods. The material for writing this article was obtained by literature study and analyzed using legal interpretation. Sharia treaty arrangements that exist and are related to undue influence elements are a form of agreement that is prohibited and forbidden until it is called ikrah. Ikrah is the coercion of the strong against the weak, while doing ikrah is a deed and disliked by God. To do ikrah is to violate the elements and conditions of trade in Islam. The legal effect of this act is a null and void agreement.